# Ln y 1 ln x 2 sin x cos x tan3 x 1 dy 3 sec2 x cot

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = −t/2 and lim(1 − 2x)1/x = lim(1 + t)−2/t = lim[(1 + t)1/t ]−2 = e−2 . 58. If t = 3/x, then x = 3/t and lim (1 + 3/x)x = lim (1 + t)3/t = lim [(1 + t)1/t ]3 = e3 . + + x→0 x→+∞ t→0 t→0 t→0 t→0 107 Chapter 4 EXERCISE SET 4.3 1. y = (2x − 5)1/3 ; dy/dx = 2. dy/dx = 1 2 + tan(x2 ) 3 3. dy/dx = 3 x−1 2 x+2 4. dy/dx = 1 x2 + 1 2 x2 − 5 5. dy/dx = x3 − 2 3 1/2 2 (2x − 5)−2/3 3 −2/3 sec2 (x2 )(2x) = 2 x sec2 (x2 ) 2 + tan(x2 ) 3 9 d x−1 x−1 = 2 x+2 dx x + 2 2(x + 2) −1/2 d x2 + 1 1 x2 + 1 = dx x2 − 5 2 x2 − 5 −1/2 −2/3 1/2 −12x 6x x2 + 1 =− 2 (x2 − 5)2 (x − 5)2 x2 − 5 (5x2 + 1)−5/3 (10x) + 3x2 (5x2 + 1)−2/3 = 12 x (5x2 + 1)−5/3 (25x2 + 9) 3 4 x2 (3 − 2x)1/3 (−2) − (3 − 2x)4/3 (2x) 2(3 − 2x)1/3 (2x − 9) = 6. dy/dx = 3 4 x 3x3 5 15[sin(3/x)]3/2 cos(3/x) [sin(3/x)]3/2 [cos(3/x)](−3/x2 ) = − 2 2x2 7. dy/dx = 8. dy/dx = − 9. 10. 1 cos(x3 ) 2 −3/2 − sin(x3 ) (3x2 ) = 32 x sin(x3 ) cos(x3 ) 2 −3/2 dy dy 2 − 3x2 − y + y − 2 = 0, = dx dx x dy 1 + 2x − x3 1 1 (b) y = = + 2 − x2 so = − 2 − 2x x x dx x 2 − 3x2 − y 2 − 3x2 − (1/x + 2 − x2 ) 1 dy = = = −2x − 2 (c) from part (a), dx x x x (a) 3x2 + x 1 −1/2 dy dy √ y − ex = 0 or = 2ex y 2 dx dx dy (b) y = (2 + ex )2 = 2 + 4ex + e2x so = 4ex + 2e2x dx dy √ = 2ex y = 2ex (2 + ex ) = 4ex + 2e2x (c) from part (a), dx (a) dy x dy = 0 so =− dx dx y 11. 2x + 2y 12. 3x2 − 3y 2 13. x2 14. x3 (2y ) dy x2 − 2y dy dy dy = 6(x + y ), −(3y 2 + 6x) = 6y − 3x2 so =2 dx dx dx dx y + 2x dy dy + 2xy + 3x(3y 2 ) + 3y 3 − 1 = 0 dx dx 1 − 2xy − 3y 3 dy dy = 1 − 2xy − 3y 3 so = (x2 + 9xy 2 ) dx dx x2 + 9xy 2 dy dy + 3x2 y 2 − 5x2 − 10xy + 1 = 0 dx dx 10xy − 3x2 y 2 − 1 dy dy (2x3 y − 5x2 ) = 10xy − 3x2 y 2 − 1 so = dx dx 2x3 y − 5x2 −1/2 Exercise Set 4.3 108 1 dy dy 1 y2 − 2 = 0 so =− 2 2 dx y x dx x 15. − 16. 2x = (x − y )(1 + dy/dx) − (x + y )(1 − dy/dx) , (x − y )2 2x(x − y )2 = −2y + 2x 17. 18. 19. cos(x2 y 2 ) x2 (2y ) 21. dy 1 − 2xy 2 cos(x2 y 2 ) dy + 2xy 2 = 1, = dx dx 2x2 y cos(x2 y 2 ) (1 + csc y )(− csc2 y )(dy/dx) − (cot y )(− csc y cot y )(dy/dx) , (1 + csc y )2 dy 2x(1 + csc y )2 = − csc y (csc y + csc2 y − cot2 y ) , dx 2x(1 + csc y ) dy but csc2 y − cot2 y = 1, so =− dx csc y 2x = 3 tan2 (xy 2 + y ) sec2 (xy 2 + y ) 2xy so 20. dy dy + y2 + dx dx =1 dy 1 − 3y 2 tan2 (xy 2 + y ) sec2 (xy 2 + y ) = dx 3(2xy + 1) tan2 (xy 2 + y ) sec2 (xy 2 + y ) dy (1 + sec y )[3xy 2 (dy/dx) + y 3 ] − xy 3 (sec y tan y )(dy/dx) = 4y 3 , 2 (1 + sec y ) dx dy multiply through by (1 + sec y )2 and solve for dx y (1 + sec y ) dy = to get dx 4y (1 + sec y )2 − 3x(1 + sec y ) + xy sec y tan y 3x d2 y (4y )(3) − (3x)(4dy/dx) 12y − 12x(3x/(4y )) 12y 2 − 9x2 −3(3x2 − 4y 2 ) dy = , = = = = , dx 4y dx2 16y 2 16y 2 16y 3 16y 3 but 3x2 − 4y 2 = 7 so 22. dy x(x − y )2 + y dy so = dx dx x d2 y −3(7) 21 = =− 2 3 dx 16y 16y 3 x2 d2 y dy y 2 (2x) − x2 (2ydy/dx) 2xy 2 − 2x2 y (−x2 /y 2 ) 2x(y 3 + x3 ) = − 2, =− =− =− , 2 4 4 dx y dx y y y5 but x3 + y 3 = 1 so d2 y 2x =− 5 dx2 y 23. y d2 y dy x(dy/dx) − y (1) x(−y/x) − y 2y =− , =− =− =2 dx x dx2 x2 x2 x 24. y dy = , dx y−x (y − x)(dy/dx) − y (dy/dx − 1) d2 y = = 2 dx (y − x)2 = 25. (y − x) y y −y −1 y−x y−x (y − x)2 y 2 − 2xy d2 y 3 but y 2 − 2xy = −3, so =− (y − x)3 dx2 (y − x)3 sin y dy d2 y dy = (1 + cos y )−1 , = = −(1 + cos y )−2 (− sin y ) 2 dx dx dx (1 + cos y )3 109 26. Chapter 4 dy cos y = , dx 1 + x sin y (1 + x sin y )(− sin y )(dy/dx) − (cos y )[(x cos y )(dy/dx) + sin y ] d2 y = 2 dx (1 + x sin y )2 =− 2 sin y cos y + (x cos y )(2 sin2 y + cos2 y ) , (1 + x sin y )3 but x cos y = y , 2 sin y cos y = sin 2y , and sin2 y + cos2 y = 1 so sin 2y + y (sin2 y + 1) d2 y =− 2 dx (1 + x sin y )3 27. 28. √ √ √ √ dy dy x = − ; at (1/ 2, 1/ 2), = −1; at (1/ 2, −1/ 2), dx y dx √ −x dy dy 2, = +1. Directly, at the upper point y = 1 − x =√ = −1 and at the lower point dx dx 1 − x2 √ x dy =√ = +1. y = − 1 − x2 , dx 1 − x2 By implicit diﬀerentiation, 2x+2y (dy/dx) = 0, √ √ If y 2 − x + 1 = 0, then y = x − 1 goes through the point (10, 3) so dy/dx = 1/(2 x − 1). By √ implicit diﬀerentiation dy/dx = 1/(2y ). In both cases, dy/dx|(10,3) = 1/6. Similarly y = − x − 1 √ goes through (10, −3) so dy/dx = −1/(2 x − 1) = −1/6 which yields dy/dx = 1/(2y ) = −1/6. dy x3 1 dy = 0, so = − 3 = − 3/4 ≈ −0.1312. dx dx y 15 29. 4x3 + 4y 3 30. 3y 2 31. 4(x2 + y 2 ) 2x + 2y dy dy dy dy y+1 + x2 + 2xy + 2x − 6y = 0, so = −2x 2 = 0 at x = 0 dx dx dx dx 3y + x2 − 6y dy dx = 25 2x − 2y dy , dx x[25 − 4(x2 + y 2 )] dy dy = ; at (3, 1) = −9/13 dx y [25 + 4(x2 + y 2 )] dx 32. 2 3 34. (a) x−1/3 + y −1/3 dy dx = 0, √ √ dy y 1/3 = − 1/3 = 3 at (−1, 3 3) dx x y 2 0 x 1 2 –2 (b) dy dy = (x − a)(x − b) + x(x − b) + x(x − a) = 3x2 − 2(a + b)x + ab. If = 0 then dx dx 2 3x − 2(a + b)x + ab...
View Full Document

## This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online